Mesangial Cell Apoptosis Induced by Stimulation of the Adenosine A3 Receptor: Signaling and Apoptotic Events. (10th December 2015) - Duann, Pu; Ho, Teh-Yuan; Desai, Bijal D.; Kapoian, Toros; Cowen, Daniel S.; Lianos, Elias A.
Abstract : Mesangial cell apoptosis has been proposed as a means of resolution of glomerular hypercellularity in proliferative forms of glomerular disease. We previously demonstrated that adenosine causes mesangial cell apoptosis by stimulating the A3 -type adenosine receptor. This is a G protein-coupled receptor shown to activate kinases involved in apoptotic signaling. In this work, we assessed changes in phosphorylation of the mitogen-activated protein kinase extracellular signal-regulated kinase (ERK)1/2 and in levels of specific pro- and antiapoptotic proteins following exposure of mesangial cells to the A3 adenosine receptor agonist N (6)-(3-iodobenzyl)-adenosine-5′- N -methyluronamide (IB-MECA). Cultured mesangial cells were incubated with IB-MECA for 30 minutes and 6, 24, and 48 hours. IB-MECA was used at a concentration (30 μM) that induces a reproducible degree of mesangial cell apoptosis. Changes in ERK1/2 phosphorylation and in protein levels of Bcl-2, Bax, and caspase 3 were assessed by Western blot analysis. IB-MECA markedly increased phosphorylation of ERK1/2. This effect peaked at 5 minutes, dissipated by 20 minutes, and was abolished by the inhibitor of ERK phosphorylation, compound U0126, in a dose-dependent manner. This inhibitor had no effect on the extent of IB-MECA-induced apoptosis. Bcl-2 levels progressively declined, whereas those of Bax and activated caspase 3 increased. These observations indicate that stimulation of the A3 -type adenosine receptor causes mesangial cell apoptosis via mechanisms independent of ERK activation. The observations also point to an imbalance in the expression of antiapoptotic (Bcl-2) and proapoptotic (Bax, caspase 3) proteins as a potential mechanism underlying adenosine-induced mesangial cell apoptosis.